2001
DOI: 10.1080/028418601750444105
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy Plus Conventional Radiotherapy or Accelerated Hyperfractionation in Stage III and IV Nasopharyngeal Carcinoma - A Phase II Study

Abstract: A prospective phase II trial was initiated in previously untreated patients with locally advanced nasopharyngeal carcinoma (NPC). The goal was to achieve improvement in locoregional control, disease-free interval and overall survival using induction chemotherapy and to compare conventional fractionation (CF) with an accelerated hyperfractionation (AHF) regimen. Fifty patients were treated (5 AJCC Stage III, 45 Stage IV) with induction chemotherapy consisting of two cycles of cisplatin and 5-fluorouracil. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In this study, we assessed the prognostic value of different clinical and pathologic assessment parameters using data of 173 cervical squamous cell carcinoma patients who underwent neoadjuvant RT or CCRT prior to radical hysterectomy. Although no standard procedures for neoadjuvant therapy plus surgery have been confirmed yet and more supporting data are still needed, especially data regarding CCRT, some studies have suggested that pre-operative CCRT is associated with significantly improved PFS and OS compared with RT alone [ 21 , 22 ], whereas other studies have provided evidence suggesting almost the same clinical outcomes following these different treatment modalities [ 13 , 23 ]. Our data also did not show significant differences in the outcomes of patients who received RT alone or CCRT, which is consistent with the results of the study by Keys et al [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we assessed the prognostic value of different clinical and pathologic assessment parameters using data of 173 cervical squamous cell carcinoma patients who underwent neoadjuvant RT or CCRT prior to radical hysterectomy. Although no standard procedures for neoadjuvant therapy plus surgery have been confirmed yet and more supporting data are still needed, especially data regarding CCRT, some studies have suggested that pre-operative CCRT is associated with significantly improved PFS and OS compared with RT alone [ 21 , 22 ], whereas other studies have provided evidence suggesting almost the same clinical outcomes following these different treatment modalities [ 13 , 23 ]. Our data also did not show significant differences in the outcomes of patients who received RT alone or CCRT, which is consistent with the results of the study by Keys et al [ 24 ].…”
Section: Discussionmentioning
confidence: 99%